RELATIONSHIP BETWEEN MATHEMATICS LEARNING INTEREST AND NUMERACY LITERACY SKILLS - Leni Agus Meria; Nur Rusliah (UIN Imam Bonjol Padang, 2025)
This study aims to analyze the relationship between students’ interest in learning mathematics and their numeracy literacy skills in the context of the Merdeka Curriculum. The study employed a quantitative approach with a correlational design involving 60 eighth-grade students of SMP Negeri 27 Kerinci selected through simple random sampling. The research instruments consisted of a mathematics learning interest questionnaire using a Likert scale and a numeracy literacy test based on contextual PISA-model items. Data were analyzed using the Pearson correlation test after the assumptions of normality and linearity were met. The results showed a correlation coefficient of r = 0.56 with p 0.05, which falls into the moderate correlation category. These findings indicate that students’ interest in learning mathematics plays a significant role in supporting numeracy literacy skills; therefore, engaging and contextual learning strategies are needed to enhance both aspects.